ANALISIS PERNYATAAN STANDAR AKUNTANSI KEUANGAN NO.34 TENTANG PENGAKUAN PENDAPATAN KONTRAK KONTRUKSI PADA PT. TANJUNG RAYA BERSAMA BANJARBARU - Maria Anastasia; Imawati Yousida; Pipit Angelina; Siti Fatimah; May Kastanika (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
The purpose of this research is to find out the Analysis of Statement of Financial Accounting Standards No. 34 Concerning Construction Contract Revenue Recognition at PT. Tanjung Raya with Banjarbaru The method used in this research is descriptive analysis technique. is an analysis technique by comparing the data obtained in the company which is the object of research with accounting theories. 34 where the company only recognizes cash basic income, so the company gets less term value and the project is short term